Academic Mentorship Builds a Pathology Community. (19th August 2015) - Gotlieb, Avrum I.
Since academic mentorship focuses on developing and supporting the next generation of pathologists as well as the existing faculty, it plays a vital role in creating a successful academic pathology department whose faculty deliver quality teaching, research, and clinical care. The central feature is the mentor–mentee relationship which is built on mutual respect, transparency, and a genuine interest from the mentor in the success of the mentee. This relationship is a platform for career development, academic guidance, informed professional choices, and problem solving. Departments of pathology must embrace a culture of effective mentorship so that trainees and faculty members are well mentored. Mentorship should become an academic activity that is valued and rewarded. Departments should create and support formal educational programs that train mentors in mentorship. Effective models of formal mentorship need to be created and evaluated in order to strengthen academic pathology. A successful mentorship culture will provide for a sustainable community of academic pathologists that transmits their best practices to the next generation.